Parents' Weekend faculty presentations in Tisch Library. Photo 034 - Arkin, Sarah (Tufts Archival Research Center, 2008)
Parents' Weekend faculty presentations in Tisch Library. "Why Students Go to College,Why Parents Send Them: Competing Views on Higher Education, Society, and Community" Susan Ostrander, professor,Department of Sociology, and University College faculty fellow; "A Community within a Community: The Building of a College Campus" John Roberto, vice president of operations; "Pursuing Environmental Justice and Sustainability in the Mystic River Watershed" Dale Bryan, assistant director,Department of Peace and Justice Studies, and experiential learning coordinator, Center for Interdisciplinary Studies; "Media and Public Service: Teaching Tufts Students to Use Media Instead of Being Used by the Media" Roberta Oster Sachs, lecturer, University College of Citizenship and Public Service; "Lost Theaters, Immigrant Stories, and African-American Memory: Community Partnership Learning in Tufts' Backyards" Rosalind Shaw, associate professor and chair,Department of Anthropology; "A Look into the Suburban Neighborhoods Where Tufts Faculty Members Live and Write: A Reading from 'An Ambulance Is on the Way: Stories of Men in Trouble'" Jonathan Wilson, Fletcher Professor of Rhetoric and Debate and professor,Department of English; "Tufts Local Action on Global Climate Change" William Moomaw, professor of international environmental policy, director of the Center for International Environment and Resource Policy; "Six Myths about American Politics" Jeffrey Berry, John Richard Skuse, Class of 1941, Professor of Political Science; "Global Citizenship from the Prisons of South Africa to Post- Tsunami Reconstruction in Sri Lanka" Sherman Teichman, director of the Institute for Global Leadership.